Perspective of patients and caregivers about stroke rehabilitation: the Quebec experience. Issue 1 (2nd January 2019) - Lamontagne, Marie-Eve; Richards, Carol; Azzaria, Leila; Rosa-Goulet, Mélany; Clément, Louise; Pelletier, France
ABSTRACT: Background : The unique perspectives of patients and caregivers on their experiences as users of rehabilitation services help identify areas for improvement for the continuum from acute care to community integration. Objective : This study reports perceptions of persons with stroke and their caregivers in an existing continuum of stroke care, social services, and rehabilitation in the Province of Quebec. Methods : A total of 10 focus groups were held, 5 with persons with stroke ( n  = 37, mean age 59.6 years (SD = 11.6); 21 men) and 5 others with caregivers ( n  = 31; mean age 58.8 years (SD = 15.1); 8 men). Discussions were transcribed and were the object of thematic content analysis using Nvivo. Results : Participants expressed their general satisfaction toward the care received in inpatient, hospital, and rehabilitation settings. The information received about acute care, however, was deemed insufficient and fragmented, and access of rehabilitation services was often perceived to be difficult. In the community integration phase of the continuum, most participants stated that they had experienced poor accessibility to services of any kind. Conclusion s: Persons with stroke and their relatives' perspectives about the services that they obtained throughout the rehabilitation continuum vary importantly according to the services examined. Adopting a continuum perspective is helpful to target priorities for improvement.